Muscle Adaptations to Heavy-Load and Blood Flow Restriction Resistance Training Methods - May, Anthony K.; Russell, Aaron P.; Della Gatta, Paul A.; Warmington, Stuart A. (Frontiers in Physiology, 2022)
Resistance-based blood flow restriction training (BFRT) improves skeletal muscle strength and size. Unlike heavy-load resistance training (HLRT), there is debate as to whether strength adaptations following BFRT interventions can be primarily attributed to concurrent muscle hypertrophy, as the magnitude of hypertrophy is often minor. The present study aimed to investigate the effect of seven weeks of BFRT and HLRT on muscle strength and hypertrophy. The expression of protein growth markers from muscle biopsy samples was also measured. Male participants were allocated to a HLRT (HL; n = 9), low-load BFRT (LL+BFR; n = 8), or passive rest (PAS; n = 9) group to control for the effect of time. HL and LL+BFR completed 21 training sessions (3 d∙wk-1) comprising bilateral knee extension and knee flexion exercises (HL = 70% one repetition maximum (1-RM), LL+BFR = 20% 1-RM + blood flow restriction). Bilateral knee extension and flexion 1-RM strength were assessed, and leg muscle CSA was measured via peripheral quantitative computed tomography. Protein growth markers were measured in vastus lateralis biopsy samples taken pre- and post the first and last training sessions. Biopsy samples were also taken from the PAS control group at the same time intervals as HL and LL+BFR. Knee extension 1-RM strength increased in HL (19%) and LL+BFR (19%) but not PAS (2%) (P < 0.05). Knee flexion 1-RM strength increased similarly between all groups, as did muscle CSA (50% femur length; HL = 2.2%, LL+BFR = 3.0%, PAS = 2.1%; TIME main effects). 4E-BP1 (Thr37/46) phosphorylation was lower in HL and LL+BFR immediately post-exercise compared with PAS in both sessions (P < 0.05). Expression of other growth markers was similar between groups (P > 0.05). Overall, BFRT and HLRT improved muscle strength and size similarly, with comparable changes in intramuscular protein growth marker expression, both acutely and chronically, suggesting the activation of similar anabolic pathways. However, the low magnitude of muscle hypertrophy was not significantly different to the non-training control suggesting that strength adaptation following seven weeks of BFRT is not driven by hypertrophy, but rather neurological adaptation.